Banks Plays a Pivotal Role in Entrepreneurship Development - Dr. Anand. K.; Dr. Naveen Kumar. H (International Journal of Engineering and Management Research, 2024)
Banks contribute significantly and positively in advising and providing loans for the development of entrepreneur in India. Banks are essential for the survival and their unique role as the engine of growth in the country. The central government organization regulates banking and non-banking financial institutions. Entrepreneurship development is a concept that has to do with the formation, financing, growth and expansion of business or enterprises in an economy. This paper focus on the role of banks in the development of entrepreneurship in Mysore. It is aimed at to find out problems faced by entrepreneurs in obtaining the loans from the banks for their startups/expansion and the major difficulties faced by the banks towards sanctioning and recovery of the loans. This paper also focused on factors considered by banks before lending loans to entrepreneurs.